EXTREME STATES: A SHOCK - P.F. Litvitsky (Вопросы современной педиатрии)
The lecture analyzes etiology and key parts of pathogenesis of a form of extreme states — a shock. Author characterizes its types and symptoms and principles of treatment and prophylaxis.Key words: sludge, disseminated formation of thrombus and fibrinolysis, «shock lungs», «shock kidney».(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(4):85-93)